2016
DOI: 10.1007/s10964-016-0418-1
|View full text |Cite
|
Sign up to set email alerts
|

How Mental Health Interviews Conducted Alone, in the Presence of an Adult, a Child or Both Affects Adolescents’ Reporting of Psychological Symptoms and Risky Behaviors

Abstract: The normative process of autonomy development in adolescence involves changes in adolescents’ information management typically characterized by decreasing disclosure and increasing concealment. These changes may have an important impact on the early detection and timely treatment of mental health conditions and risky behavior. Therefore, the objective was to extend our understanding of how these developmental changes in adolescent disclosure might impact adolescent mental health interviews. Specifically, we es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Alternatively, the variation could be attributed to the younger age range and the use of random sampling in the present study, or because participants were not interviewed alone. Both depressive symptomatology and risky behaviours have been negatively associated with disclosure when an adult is present, thus adolescents may have underreported depressive symptoms in our study [59].…”
Section: Plos Global Public Healthmentioning
confidence: 74%
“…Alternatively, the variation could be attributed to the younger age range and the use of random sampling in the present study, or because participants were not interviewed alone. Both depressive symptomatology and risky behaviours have been negatively associated with disclosure when an adult is present, thus adolescents may have underreported depressive symptoms in our study [59].…”
Section: Plos Global Public Healthmentioning
confidence: 74%
“…For example, while high levels of alcohol use might be a contributing factor in attempted suicide (i.e., by reducing inhibitions) [ 34 , 35 ], SAs might lead to increased alcohol consumption as a method of self-medication. It is also possible other variables account for this association (poverty, sexual abuse and prior mental disorders such as depression, among others) [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may have significant implications for the current study given that about one third of the subsample identified as Hispanic or Latino and this subgroup also reported more institutional sanctions than Caucasian or African American participants. There is also evidence that adolescents report fewer PTSD symptoms when an adult is present during the computer-assisted CIDI (Herrera, Benjet, Méndez, Casanova, & Medina-Mora, 2017); it is unclear how many interviews were completed with an adult present in the Pathways study, but this is another potential contributor to reduced endorsement.…”
Section: Discussionmentioning
confidence: 99%